1979
DOI: 10.1136/gut.20.11.1020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of proximal gastric vagotomy and anticholinergics on the acid and gastrin responses to sham feeding in duodenal ulcer patients.

Abstract: SUMMARY Plasma gastrin concentrations and gastric acid output after modified sham feeding were determined in 20 duodenal ulcer patients. Sham

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

1980
1980
1993
1993

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…They found a significant rise of serum gastrin level during MSF, either in the case of simple aspiration of gastric juice or maintaining the gastric content at pH 5.0 by intragastric titration. Stenquist et al (1979) reported, however, no significant rise of plasma gastrin without using the intragastric titration technique like in our study. These discrepancies are difficult to explain, but may be due to differences in doses of atropine, sham feeding technique and with or without the use of intragastric titration.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…They found a significant rise of serum gastrin level during MSF, either in the case of simple aspiration of gastric juice or maintaining the gastric content at pH 5.0 by intragastric titration. Stenquist et al (1979) reported, however, no significant rise of plasma gastrin without using the intragastric titration technique like in our study. These discrepancies are difficult to explain, but may be due to differences in doses of atropine, sham feeding technique and with or without the use of intragastric titration.…”
Section: Discussioncontrasting
confidence: 42%
“…Konturek et al (1978Konturek et al ( , 1980Konturek et al ( , 1981 and Stenquist et al (1979) did not find an increase of plasma gastrin concentration after sham feeding, while Feldman et al (1979) and Feldman and Walsh (1980) reported contrary. They found a significant rise of serum gastrin level during MSF, either in the case of simple aspiration of gastric juice or maintaining the gastric content at pH 5.0 by intragastric titration.…”
Section: Discussionmentioning
confidence: 70%
“…Modified sham feeding seems to adequately reflect normal physiological vagal activation of gastric secretion (18), which was confirmed by the observation that complete vagotomy abolished the acid response to sham feeding (19,20). The pathological mechanisms of stress ulceration nave otten been attnbuted to gastric hypersecretion (21)(22)(23).…”
Section: Discussionmentioning
confidence: 72%
“…This antimuscarinic drug was chosen since it is known not to pass the blood-brain barrier. The larger dose used has previously been shown to inhibit the acid response to shamfeeding in man by about 65%, whereas a further increase in dose did not induce a more profound inhibition [4]. A 10 times lower dose of benzilonium bromide was also investi gated in view of the previously obtained results with low doses of atropine [4,5], indicating a susceptibility of inhibitory vagal fibers to even minute amounts of an antimuscarinic substance.…”
Section: Patientsmentioning
confidence: 99%
“…In man physiological vagal stimulation has been re ported to induce a small but significant gas trin response [2,3], whereas others have ex perienced difficulties in demonstrating any effect [4], In this context it seems relevant to point out that the vagus nerve exerts a dual action on the gastrin cells in the antrum, the most predominant one being of inhibitory nature [2. 5, 6], In addition, experiments in dogs have also suggested an inhibitory mech anism operating on the gastrin cells at least partly via local nervous reflexes from the fundic region [7], suggesting complex ner vous control of gastrin secretion.…”
mentioning
confidence: 99%